12 - 3 = 9
3 + 9 = 12
12 - 9 = 3
F( x ) = ( x - 1 ) ( x + 2i )( x - 2i ), because the zeroes are 1, -2i, +2i ;
f( x ) = ( x - 1 )( x^2 - 4i^2 ) = ( x - 1 )( x^2 + 4 ) = x^3 - x^2 + 4x - 4 ;
Answer: See attachment below (graphing)
Step-by-step explanation:
<u>INFORMATION:</u>
The slope-intercept is when y=mx+b
mx=the slope
b=y-intercept
<u />
<u>REPHRASE EQUATION:</u>
y=mx+b
y=-3-x
y=(-1)x-3
<u>CONCLUSION:</u>
Slope=-1
Y-intercept=-3
Hope this helps!! :)
Please let me know if you have any questions
3 different ones. M-N-& P. Please